Analgesic Effects Elicited by Neuroactive Mediators Injected into the ST 36 Acupuncture Point on Inflammatory and Neuropathic Pain in Mice - Jádina S. Vieira; Jéssica A. Toreti; Ravena C. de Carvalho; João E. de Araújo; Marcelo L. Silva; Josie R.T. Silva (Medical Association of Pharmacopuncture Institute, 2018)
The present study evaluates whether the injection of serotonin, acetylcholine, glutamate, bradykinin, histamine, or substance P (SP) into the Zusanli (Stomach 36, ST 36) acupoint can also produce the acupuncture-induced antinociceptive effect on inflammatory or neuropathic pain. In this in vivo experimental study, a total of 450 male Swiss mice were used. Mice were injected with saline or complete Freund's adjuvant (CFA) or subjected to sham or chronic constriction injury (CCI) surgery. After the establishment of the inflammatory (4 hours) or the neuropathic pain (3 days), the animals (n = 6) received manual acupuncture, sham acupuncture, or injection of saline, serotonin, acetylcholine, glutamate, bradykinin, histamine, or SP into the ST 36 and were evaluated for up to 24 hours. Mechanical threshold was evaluated, and the L4-L6 dorsal root ganglion was used for analysis of the transient receptor potential vanilloid type 1 overexpression. The mice from both the CFA and CCI models treated with manual acupuncture had significant increases in the thresholds for more than 24 hours. Sham acupuncture stimulation did not change the thresholds. In the mice injected with each of the mediators, the thresholds were significantly increased for all times in both the CFA and CCI models. Transient receptor potential vanilloid type 1 overexpression in CFA and CCI mice was reduced at all times by injection of serotonin, acetylcholine, or SP but not by injection of glutamate, histamine, or bradykinin. Our data suggest that the neuroactive mediators released by acupuncture-induced tissue injury may contribute to acupuncture-induced analgesia. Keywords: acupuncture-induced analgesia, inflammatory pain, neuroactive mediators, neuropathic pain